EVALUASI DAMPAK PENGGUNAAN SISTEM INFORMASI GEOGRAFIS (SIG) DALAM PENGELOLAAN SUMBER DAYA ALAM DAN PENGALIHAN KEBIJAKAN PUBLIK DI DAERAH RAWAN BENCANA ALAM - Adi, Bagas Daniswara (STKIP Persada Khatulistiwa Sintang, 2024)
This research aims to evaluate the impact of Geographic Information System (GIS) implementation in natural resource management and disaster risk mitigation in natural disaster-prone areas. Using a case study approach in several disaster-prone areas in Indonesia, this research analyses how GIS can improve the efficiency of disaster risk mapping, natural resource management, and more sustainable spatial planning. Qualitative methods were used, including in-depth interviews, focus group discussions (FGDs) and participatory observation to analyse GIS implementation, technical challenges and cross-sector collaboration. The results showed that GIS improved the accuracy of risk mapping, accelerated disaster response from >72 hours to <24 hours, and strengthened data-driven decision-making. However, constraints such as limited technological infrastructure, human resource capacity, and budget are still major challenges. This research suggests the need for close collaboration between the government, research institutions and the private sector, as well as improved technical training for policy makers to utilise GIS effectively. In the future, exploring the integration of GIS with artificial intelligence and blockchain technology could improve the efficiency and transparency of disaster management.